2008
DOI: 10.1016/j.paid.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between low positive affectivity and behavioral inhibition in preschool-age children: A comparison of behavioral approach in novel and non-novel contexts

Abstract: The temperament constructs of low positive affectivity (PA) and high behavioral inhibition (BI) overlap and are often not differentiated in the research literature. In particular, both constructs are characterized by low approach and engagement. However, current theoretical conceptualizations of these constructs suggest that low PA should be associated with low approach across most contexts, whereas BI should be associated with low approach only in novel situations. The present study used laboratory measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…There is some conceptual overlap between high BI and low PE, as both include low approach/engagement. However, in low PE these features are present across contexts, whereas in BI, they reflect context-specific behavior in novel and/or threatening situations (Henderson et al, 2004; Laptook et al, 2008; Laptook et al, 2010). In the present study, correlations between BI and PE were substantial for parent-report measures, but negligible using laboratory-based measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some conceptual overlap between high BI and low PE, as both include low approach/engagement. However, in low PE these features are present across contexts, whereas in BI, they reflect context-specific behavior in novel and/or threatening situations (Henderson et al, 2004; Laptook et al, 2008; Laptook et al, 2010). In the present study, correlations between BI and PE were substantial for parent-report measures, but negligible using laboratory-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although there is overlap between these constructs (e.g., both BI and low PE are related to low approach and both BI and high NE include fear/anxiety) they are distinguishable (Durbin, Klein, Hayden, Buckley, & Moerk, 2005; Kim et al, 2011; Laptook, Klein, Olino, Dyson, & Carlson, 2010). Unlike low PE, which is evident across contexts, BI is observed primarily in novel and threatening situations (Henderson, Marshall, Fox, & Rubin, 2004; Laptook et al, 2008; Laptook et al, 2010). Unlike BI, high NE includes dysphoric qualities such as sadness and irritability and is considered a much broader and less context-specific trait.…”
mentioning
confidence: 90%
“…However, even conceptions that focus on narrower constructs, such as BI or shyness, appear to represent complex configurations of traits. BI includes elements of both high NE and low positive emotionality (Laptook et al, 2008), and shy behavior can reflect high anxiety (social-evaluative shyness), isolation emerging from peer rejection, or low social Downloaded by [Umeå University Library] at 21:17 05 April 2015 interest (Asendorpf, 1993). To provide a more coherent target for linkage with neurobiological constructs, it will be important to understand the nature and structure of dimensions underlying fear proneness, taking into account developmentally appropriate manifestations of fear.…”
Section: Defensive Reactivity and Cognitive Control As Core Neurobehamentioning
confidence: 99%
“…However, there has been a recent interest in the development of positive affect and temperamental exuberance (Dennis, 2006; Rydell, Thorell, & Bohlin, 2007; Stifter et al, 2008). Though exuberance is associated with low levels of both behavioral inhibition and social wariness (i.e., uninhibited behavior, Fox et al, 2001), there is evidence to suggest that these approach biases represent an orthogonal, independent temperamental construct (Dennis, 2006; Laptook, Klein, Durbin, Hayden, Olino & Carlson, 2008; Pfeifer et al, 2002), associated with distinct outcomes. Therefore, the current study examined patterns of exuberance across early childhood, as well as the role of frontal EEG asymmetry in differentiating adaptive and maladaptive social-emotional outcomes for high exuberant children.…”
Section: Longitudinal Stability Of Temperamental Exuberance and Sociamentioning
confidence: 99%
“…These profiles were also distinguished by latency to touch novel toys throughout infancy and concurrent behavior problems (Putnam & Stifter, 2005). Furthermore, work has shown that behavioral inhibition or low approach behavior is present when negative affect is high, but there is little positive affect present (Laptook et al, 2008; Park et al, 1997). Thus, the combination of positive affect and approach seems to define exuberant behavior.…”
Section: Longitudinal Stability Of Temperamental Exuberance and Sociamentioning
confidence: 99%